A Dynamic Model for Managing Volunteer Engagement - Ata, Baris; Tongarlak, Mustafa H.; Lee, Deishin; Field, Joy (Operations Research, 2024)
Managing Volunteer Engagement Non-profit organizations that provide food, shelter, and other services to people in need, rely on volunteers to deliver their services. Unlike paid labor, non-profit organizations have less control over unpaid volunteers’ schedules, efforts, and reliability. However, these organizations can invest in volunteer engagement activities to strive for a steady and adequate supply of volunteer labor. The paper, “A Dynamic Model for Managing Volunteer Engagement”, models the volunteer management process. The paper derives a dynamic control policy that judiciously uses the non-profit’s resources for volunteer engagement activities depending on explicit congestion thresholds, thereby lowering the overall cost of the non-profit operation.